PENGARUH PEMBERIAN MAKANAN TAMBAHAN (PMT) NUGGET TEBELO (TELUR BEBEK KELOR) TERHADAP PENINGKATAN BERAT BADAN BALITA USIA 3-5 TAHUN DI KLINIK PRATAMA KASIH IBU KECAMATAN DELI TUA TAHUN 2025 - Sriwahyuni, Eka; Siregar, G.F Gustina; Ramadany, Rani (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2025)
The Toddler is a golden period of growth and development, which is highly influenced by adequate nutritional intake. Nutritional problems sucs as underweight, wasting, and stunting remain serious public health concerns that effect child growth. These issues are still prevalent in Indonesia, including in Deli Serdang Regency. Deficiencies in macro and micro nutrients sucs as protein, iron, and zinc can lead to growth disorders, one of which is low body weight. This study aimed to analyze the effect of providing supplementary food (PMT) in the form of TEBELO Nuggets ( duck eggs and moringa leaf) on weight gain among toddlers aged 3 – 5 years at Klinik Pratama Kasih Ibi in Deli Tua Districk in 2025. The nuggets were made from duck eggs and moringa leaf flour. The method employed a quantitative approach using a Quasi-Experimental method with a Two group pretest – posttest design. A total sample og 30 toddlers was divided into two groups : 15 in the intervention group and 15 in the control group. The intervention was carried out in April 2025 for 14 days in the form of nuggets rich in protein duck egg and rich in vitamins, minerals, and antioxidants from moringa leaves. Results from the Paired Sample T-Test showed a significant difference p value = 0.000, (p value < 0,05 ), indicating that the average weight gain in the intervention group was about 0,7 kg ( from 12,04 kg to 12,74 kg ), while the control group only gained an average of 0,18 kg. These findings demonstrate that PMT with TEBELO nuggets has significant effect on increasing toddlers weight. This studiy highlights the potensial of using local-based PMT innovations to toddles malnutrition and recomends implementation through community-based program such us Ingrated Health service Post and Community Health Center.